Remotely sensed solutions for plant diversity conservation - Baena, Susana (2018)
Global change is happening at a staggering pace and the impact that change is having in the loss of plant biodiversity is unprecedented. The latest reports on the state of the world’s plants indicate that they face intensifying threats and biodiversity loss on a global scale. However, this rapid global change is also bringing extraordinary technological developments to all scientific fields. Earth Observation by Remote Sensing is undergoing a fast expansion and its capacity to monitor and analyse global environmental changes and their impact in biodiversity is ever growing. This research analyses the current and potential role of Earth Observation in the conservation of plant diversity, identifying the latest technological developments with the greatest potential use in this field. Looking into a plant conservation organisation and through a series of case studies covering a range of spatial and temporal scales, this research brings the latest Remote Sensing technology to the plant conservation community. From collecting and processing very high resolution data for local conservation projects to help determine conservation status of a country’s unique ecosystem to tracking and reporting on global plant conservation targets this research demonstrates that Remote Sensing is instrumental for addressing the observation needs of the plant conservation community.